2016
DOI: 10.1128/jb.00711-15
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome-Wide Identification of Hfq-Associated RNAs in Brucella suis by Deep Sequencing

Abstract: Recent breakthroughs in next-generation sequencing technologies have led to the identification of small noncoding RNAs (sRNAs) as a new important class of regulatory molecules. In prokaryotes, sRNAs are often bound to the chaperone protein Hfq, which allows them to interact with their partner mRNA(s). We screened the genome of the zoonotic and human pathogen Brucella suis 1330 for the presence of this class of RNAs. We designed a coimmunoprecipitation strategy that relies on the use of Hfq as a bait to enrich … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 65 publications
1
22
0
Order By: Relevance
“…S11). We performed RIP‐Seq (RNA‐immunoprecipitation) experiments without crosslinking using KhpA‐L‐FLAG 3 or KhpB‐L‐FLAG 3 as bait to demonstrate that KhpA and KhpB indeed bind to RNA in cells (see Experimental procedures) (Saadeh et al ., ). We used the ratio of RNA reads obtained for each of the FLAG‐tagged strains compared to the untagged wild‐type strain as the criterion for RNA binding of RNA to KhpA or KhpB (Supporting Information Table S4).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…S11). We performed RIP‐Seq (RNA‐immunoprecipitation) experiments without crosslinking using KhpA‐L‐FLAG 3 or KhpB‐L‐FLAG 3 as bait to demonstrate that KhpA and KhpB indeed bind to RNA in cells (see Experimental procedures) (Saadeh et al ., ). We used the ratio of RNA reads obtained for each of the FLAG‐tagged strains compared to the untagged wild‐type strain as the criterion for RNA binding of RNA to KhpA or KhpB (Supporting Information Table S4).…”
Section: Resultsmentioning
confidence: 97%
“…Several general conclusions emerged from the RIP‐Seq experiments. With a fourfold enrichment as the cutoff (Saadeh et al ., ), KhpA or KhpB pulled down a remarkable overlapping set of ≈170 mRNA, tRNAs, intergenic RNAs and putative sRNAs (Fig. ; Supporting Information Table S4).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, sRNAs can regulate gene expression and/or allow for rapid alterations to encounter stimuli and stress (30). While more than 200 sRNAs have been experimentally validated in bacteria, such as Salmonella enterica and E. coli, only 5 sRNAs from Brucella have been studied so far (31,32). In the present study, we identified and validated mRNA-AbcR sRNA interactions with B. melitensis target mRNAs (which belong to the transcription regulator family), as well as Two-component response regulators.…”
Section: Discussionmentioning
confidence: 77%
“…Hfq protein, encoded by the BMEI0872 gene is an important RNA chaperone involved in stress resistance and Brucella virulence in both macrophage and mice infection models (19). Furthermore, recent studies have demonstrated that this chaperone can regulate virB operon expression and plays a key role in the interaction between sRNAs and their target mRNAs (20,21). Downregulation of this gene in our mutant strain therefore indicates a reduction in virulence relative to the parental line.…”
Section: Discussionmentioning
confidence: 81%